Evaluating the discontinued traditions of Malay wood carvings in Malaysia: a failure to develop the discourse on modern and post modern ornamentation in architectural works - Utaberta, Nangkula; Mohamad Rasdi, Mohamad Tajuddin (Science Publications, 2014)
The main intention of this study is to contribute some thoughts on why the tradition of wood carvings in traditional Malay architecture was discontinued at the rise of modern and post-modern architectural works in Malaysia. Although the tradition of wood carvings more or less came to a stop in public architectural works with the development of colonial architecture, this study seeks to clarify the modernistic and post-modern arguments on the problem or issues of ornamentation. Although modernism mainly or seemingly rejected the use of ornaments, there was still a strong strand of its development in the architecture of Frank Lloyd Wright. The western post-modernist architects such as Michael Graves and Charles Jencks went on to develop a discourse on ornamentation under the area of architectural meaning and linguistics. It is expected that this critic paper can segragate and analyse issues and problems of Malay wood carvings and start a further discussion on the development of this traditional heritage which can contribute and reconstruct a better framework for the Architectural Identity of Malaysia.